A Five Year strategic financial plan for summit sigma sigma Ready Mix Concrete Corporation - Balcita, Ian Reeve C., Balmoja, Justin Ray L., Basa, Nicasio B., Bautista Cyrus Jherald G., Clemente, Micah C., Cunanan, Aira Jhane D., Del Rosario, Erica Mae R., Galyay, Rosemarie P., Songco, A.J. F., Unso, Rosangelika Sofia A., Valerio, John Mark 4 0 16; 5
EXECUTIVE SUMMARY This report contains a five-year analysis of the performance of the entity and its financial operations. The analysis on the profitability, liquidity, stability, and other inclusive financial overall performance of the entity is based on the 5-year audited financial statement of Summit Sigma Ready Mix Concrete Corporation. The Sigma Ready Mix Concrete Corporation is a Filipino-owned corporation established in 2006 as a manufacturer of Ready-Mix concrete products and related services. It was formed as a joint venture between Summit Concrete, Inc. (Ready-mix Concrete Batching Plant) and Sigma 6 Ventures (Marketing and Sales Company). Its mission is to supply ready mix concrete to the exacting standards of the clients with exceptional and reliable service through sustainable and safe business practices.
Financial Plan: (BSBA major in Financial Management) - Pamantasan ng Lungsod ng Maynila, 2021
Keywords: 2 -- 0; 6; 20; 20; 2